ANALISIS FAKTOR-FAKTORYANG MEMPENGARUHI PENYALURAN KREDIT PADA BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2014)
The aim of this study was to analyze the effect of deposit from third parties, capital adequacy ratio, non performing loan, return on assets and Bank Indonesia certificates. The research object is the Banking Companies listed on the Indonesia Stock Exchange (IDX) in year 2010 to 2012. Samples taken in this study were as many as 25 banking companies. The sampling technique used was purposive sampling. The method of analysis used in this study is that by using multiple linear regression method  requires normality test, the classical assumption examination which consist of multicollinearity test, heteroscedasticity test, and autocorrelation test and strength test models consisting of: coefficient of determination test and F test. Hypothesis testing using t- statistic. The results of this study indicate that the variable deposit from third parties showed significant positive effect to total of loans. The variable capital adequacy ratio, non performing loan, and Bank Indonesia certificates were not significant negative effect to total of loans. Return on assets variable is not significant positive effect to total of loans. Keywords: deposit from third parties, capital adequacy ratio, non performing loan, return on sssets, Bank Indonesia certificates, and Loans